Efektivitas Program Sahabat Saksi dan Korban dalam Memenuhi Hak Masyarakat Korban Kekerasan - Windiyastuti, Feny; Syam, Radian; Heliany, Ina; Dynanti, Rana Syndri; Lase, Renungan Syukur Berkat (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2025)
The Sahabat Saksi dan Korban (Friends of Witnesses and Victims) program is part of the 2025 Beginner Community Service Program implemented in Manggarai Village, Tebet District, South Jakarta. The program aims to strengthen protection and the fulfillment of victims’ rights through a community-based approach. Using a participatory descriptive qualitative method, the activities involved observation, interviews, documentation, and joint reflection with the community. The findings show that the program enhanced community legal awareness regarding victims’ rights, reporting mechanisms, and access to protection. It also contributed to psychosocial recovery, fostered social solidarity, and reinforced local protection networks through collaboration with LPSK and the IBLAM Legal Aid Institute. A field narrative illustrated the complexity of community roles in supporting victims amid stigma and cultural barriers. Supporting factors included community leaders’ involvement and institutional support, while social stigma remained the main obstacle. These findings suggest that the Sahabat Saksi dan Korban program is effective as a community-based model for victim protection and relevant to be replicated in other urban areas with similar vulnerabilities.